2020
DOI: 10.1093/scan/nsaa074
|View full text |Cite
|
Sign up to set email alerts
|

Dissociable neural signatures of passive extinction and instrumental control over threatening events

Abstract: Aberrant fear learning processes are assumed to be a key factor in the pathogenesis of anxiety disorders. Thus, effective behavioral interventions to reduce dysfunctional fear responding are needed. Beyond passive extinction learning, instrumental control over threatening events is thought to diminish fear. However, the neural mechanisms underlying instrumental control—and to what extent these differ from extinction—are not well understood. We therefore contrasted the neural signatures of instrumental control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 40 publications
(60 reference statements)
3
15
0
Order By: Relevance
“…Interestingly, during the presentation of the indicator (i.e., anticipation without stress), participants showed more activation in the vmPFC when an uncontrollable trial was signalled, but under stress they subsequently displayed enhanced vmPFC recruitment when they knew they could terminate the stressor. Although the former finding replicates results by Wanke & Schwabe (2020b), the apparent reversal in vmPFC recruitment induced by aversive stimulation encourages further research into timingdependent effects.…”
Section: Neuroimaging Resultssupporting
confidence: 60%
See 3 more Smart Citations
“…Interestingly, during the presentation of the indicator (i.e., anticipation without stress), participants showed more activation in the vmPFC when an uncontrollable trial was signalled, but under stress they subsequently displayed enhanced vmPFC recruitment when they knew they could terminate the stressor. Although the former finding replicates results by Wanke & Schwabe (2020b), the apparent reversal in vmPFC recruitment induced by aversive stimulation encourages further research into timingdependent effects.…”
Section: Neuroimaging Resultssupporting
confidence: 60%
“…The overall down-regulatory effect that stress exerts on the vmPFC may well have prevented putative differences from reaching suprathreshold levels. In fact, studies that have found the expected condition-dependent connectivity patterns in humans have largely focused on anticipatory responses rather than investigating blood-oxygen-level-dependent (BOLD) signalling under acute stress (Kerr et al, 2012; Wanke & Schwabe, 2020b). Because the fixation phase in our design captures participants’ neural responses just before they were prompted to terminate the stressor, it effectively also constitutes an anticipatory phase, albeit under acute stress.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, participants make finger key-pressing responses to control icons on a monitor that are unrelated to the participants' bodily self. While some of the studies demonstrated the fear alleviating effect of active avoidance (Boeke et al, 2017;Delgado, Jou, LeDoux, & Phelps, 2009;Hartley et al, 2019Hartley et al, , 2014Wanke & Schwabe, 2020), the role of actual body movements awaits direct examination. Body movements are still well-required to defend against various real-life threats even in the modern human world -such as violent persons, looming vehicles, and various natural disasters.…”
Section: Introductionmentioning
confidence: 99%